Class Politics and Social Protection: A Comparative Analysis of Local Governments in India. (August 2019) - Roy, Indrajit
Dramatic differences in the quality of human life are a prominent feature of today's world. In response, many governments and international development agencies have begun to formulate and implement agendas for social protection. Nevertheless, the outcomes of such initiatives remain vastly varied. What explains such variations? In this article, I direct attention to the role of class politics in shaping the implementation of social protection by local governments that implement India's Mahatma Gandhi National Rural Employment Guarantee Act (MGNREGA). Based on a synthesis of official data, interviews with beneficiaries of social protections and elites, and direct observations in two Indian States, the author illustrates the ways in which variations in class politics influence the supply of employment works. This article departs from existing analysis of factors that favour the implementation of social protections, namely commitment of bureaucrats and politicians, political party linkages and clientelism, and civil society activism. It also nuances extant class-focused analysis which tend to adopt a polarized model of class conflict between dominant classes and the laboring poor. This article, by contrast, appreciates the conflicts within dominant classes, and emphasizes the role of coalitions and competitions between elite fractions. Where elite fractions successfully co-opt or eliminate one another, they successfully sabotage the labour-friendly MGNREGA. On the other hand, where elite fractions conflict with one another, labour-friendly programs such as the MGNREGA have a chance of being implemented. However, the transformative aspect of the program's intent, in terms of dissolving the relations of power that bolster poverty, appears to be more in evidence in localities where precarious elites align with the laboring poor to challenge the influence of the entrenched elites. As we examine alternative means of addressing the dramatic differences in the quality of life that continue to blight the contemporary world, the imperative to analyze class politics becomes greater than ever before.